173k views
4 votes
Solve the system by substitution. x= x= \,\,-y-5 −y−5 -3x+7y= −3x+7y= \,\,-45 −45

1 Answer

3 votes

Answer:

(1, -6)

Explanation:

the layout of your question is kind of confusing, but i'm guessing this is the system of equations

x = -y - 5

-3x + 7y = -45

plug in x to the second equation

-3(-y - 5) + 7y = -45

distribute

3y + 15 + 7y = -45

combine like terms

10y = - 60

divide by 10

y = -6

plug y into first equation

x = -(-6) - 5

x = 6 - 5

x = 1

User Cadell Christo
by
5.2k points